As we conduct the treatment versus dysfunctional bleeding - Giampietro, A. (2015)
Dysfunctional bleeding in women appear at different times in their sexual life, at its beginning or end of it. It may also be in the active sexual life. We focus our discussion to treat them, as follows: At puberty, Para-puberty and adolescence, at the beginning of menopause and post-menopause, and women in active sexual life.